Does the Winner Take It All? Redistributive Policies and Political Extremism - Gianmarco Daniele; Amedeo Piolatto; Willem Sas (Center for Economic Studies and ifo Institute (CESifo), 2020)
We show that regional heterogeneity of underlying fundamentals (e.g. economic history, geography, social capital) can lead to extreme voting in federations. When the outcome of federal policies – such as transfer schemes, market regulation or migration laws – depends on these fundamentals, the set of regions that wins or loses from a given policy is fixed. This gives voters a strategic incentive to distort the policy magnitude, by electing federal representatives that are extremely protective of regional interests. Interestingly, the benefits of selecting tough negotiators outweigh those of belonging to the ruling coalition. We test our predictions by looking at parties' performances at national and European Parliament elections from 1990 onwards, and find that strategic voting is indeed U-shaped: winning and losing member states vote more extremely than those in the middle. Our online survey provides further evidence.
Keywords: D72; H60; H71; H77; 330; political extremism; interregional redistribution; federalism; strategic delegation; bargaining; coalitions; EU elections; Euroscepticism; populism